Rancang Bangun Sistem Informasi Manajemen Inventarisasi Baglog Batalyon C Pelopor Satbrimob Polda Jateng Secara Qr Code - Indrastata, Ilham Buyung; Maulindar, Joni; Atina, Vihi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Batalyon C Pelopor of Central Java Satbrimob is a Polri agency unit under the auspices of the Brimob Unit Commander. This unit also has the task of fostering and improving personnel capabilities. The personnel of this unit are equipped with adequate special equipment for their duties. The logistics section inventory provides special equipment or other equipment needed while on duty, but problems were found in the manual inventory processing. In general, the design of this inventory management information system aims to provide information system management that can help manage logistics inventory with the prototype method and combine it with QR Code, in order to provide updates on the borrowing process, returns and valid results reports to the leadership. In research using the prototype method, there are several stages, including communication, quick plan, quick design modeling, construction of prototype, and deployment, delivery, and feedback. The development system in the form of a prototype that has been used in this study functions to help solve problems so that an Inventory Management Information System can be designed, built and proven to run well. The research results can be in the form of an inventory management information system for the logistics section of the Batalyon C Pelopor to implement borrowing (outgoing) and returning (incoming) activities, as well as valid report results addressed to the agency leadership.